2019
DOI: 10.1111/ejh.13236
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular features of patients with prefibrotic primary myelofibrosis previously diagnosed as having essential thrombocythemia in Japan

Abstract: Objective: Prefibrotic/early primary myelofibrosis (pre-PMF) and essential thrombocythemia (ET) exhibited different features of bone marrow; however, this is not always easy to judge objectively, making pathologists' distinction often suboptimal. In the WHO 2008 criteria, pre-PMF was not defined as a subgroup of PMF; therefore, affected patients were at a higher risk of misdiagnosis with ET. In this study, we examined the prevalence of pre-PMF patients among those previously diagnosed with ET in Japan. Method:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…In the present study, we reviewed the clinical, haematologic, and molecular parameters of patients who were diagnosed with ET, pre-PMF, and overt PMF according to the 2016 revised WHO criteria. A body of evidence has been produced by several groups indicating that pre-PMF presents more aggressive features than ET but milder features than overt PMF (3,7,8,(10)(11)(12)(13)(14). We observed that pre-PMF patients had higher leukocytes, LDH values, and splenomegaly frequency than ET patients and higher platelet counts and haemoglobin levels than overt PMF patients, consistent with historical literature, verifying the value of clinical and haematologic parameters in the precise diagnosis of pre-PMF.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, we reviewed the clinical, haematologic, and molecular parameters of patients who were diagnosed with ET, pre-PMF, and overt PMF according to the 2016 revised WHO criteria. A body of evidence has been produced by several groups indicating that pre-PMF presents more aggressive features than ET but milder features than overt PMF (3,7,8,(10)(11)(12)(13)(14). We observed that pre-PMF patients had higher leukocytes, LDH values, and splenomegaly frequency than ET patients and higher platelet counts and haemoglobin levels than overt PMF patients, consistent with historical literature, verifying the value of clinical and haematologic parameters in the precise diagnosis of pre-PMF.…”
Section: Discussionsupporting
confidence: 89%
“…Patients with pre-PMF presented with higher haemoglobin levels, higher platelet counts, higher leukocyte counts, lower LDH values, lower frequencies of splenomegaly, lower incidences of constitutional symptoms, lower circulating blast percentages, and lower IPSS risk categories than those with overt PMF (10)(11)(12). In terms of genetic mutations, several studies have implied that patients with pre-PMF have a higher incidence of driver molecular mutations (JAK2, CALR, or MPL), high-molecular-risk (HMR) mutations (ASXL1, EZH2, SRSF2, or IDH1/2), and a higher JAK2V617F allele burden than patients with ET (3,8,13,14). On the other hand, compared with overt PMF, a previous study revealed that HMR mutations were less represented in pre-PMF (10); however, another study asserted that there was no signi cant difference in the distribution of HMR mutations (11).…”
Section: Introductionmentioning
confidence: 99%
“…ASXL1 mutations are poor prognostic factors for PMF [30]; a positive correlation between the positivity of the ASXL1 mutation and the bone marrow fibrosis grade has been reported [31]. We also previously showed that the number of prefibrotic PMF patients harboring ASXL1 mutations was significantly higher than that of patients with essential thrombocythemia, which is one of the subtypes of MPNs with a milder clinical presentation than PMF [32]. These findings imply that ASXL1 mutations are associated with an adverse prognosis in overt and prefibrotic PMF patients.…”
Section: Discussionmentioning
confidence: 84%
“…In a recent study of 278 patients with pre‐PMF and 421 patients with ET, the median durations of survival in the two groups were 14.7 and 30.2 years, respectively (hazard ratio, 2.7; 95% confidence interval, 1.9‐3.7) 15 . Another study confirmed differences in the clinical manifestations of pre‐PMF and ET, such as the risks of bleeding and thrombosis 16 . Pre‐PMF gradually progresses to overt‐PMF and acute leukemia, whereas ET does not 2,15,17 .…”
Section: Discussionmentioning
confidence: 86%